Enlightening Hidden Nursing Care in Nurse-Led Clinics and See & Treat: An Observational Multicenter Protocol Study in Italy - Francesco Zaghini; Valeria Caponnetto; Manuele Cesare; Marco Di Nitto; Ilaria Marcomini; Paolo Iovino; Yari Longobucco; Annamaria Bagnasco; Loreto Lancia; Duilio Fiorenzo Manara; Laura Rasero; Gennaro Rocco; et al. (Nursing Reports)
Background/Objectives: The limited and inconsistent adoption and regulation of nurse-led clinics (NLCs) and “See & Treat” (S&T) services in Italy needs to be explored considering their value towards patients’ outcomes acknowledged in the literature. This study aims to explore the phenomenon of hidden nursing activities (HNAs) in these settings, hypothesizing that features and activities performed in these settings are heterogeneous across the country and widely underreported or attributed to other professionals than nurses. HNAs are hypothesized to be associated with a poor work environment climate and nurses’ low job satisfaction. Methods: A multicenter, cross-sectional study will be conducted across exclusively nurse-led NLC and S&T services in public health care facilities in Italy. Data collection will involve inputs from organization or nursing managers, coordinators, head nurses, and employed nurses. Information will be gathered on organizational structure, service provision, access modalities, nurses’ perceptions of their work environment, and the health care activities performed. Surveys will be distributed online to collect retrospective data in 2023 and via paper to collect 1-month prospective data about services’ activities. Expected results: This study is expected to reveal HNAs in NLC and S&T, with implications for policy, resource allocation, reimbursement models, and patient outcomes, ultimately supporting healthcare reforms and enhancing nursing’s visibility and impact in Italy. The findings will be essential for guiding health care resource allocation and shaping educational and regulatory policies that recognize and formalize the role of nurses in advanced practice. Policymakers could leverage the findings of this study to promote the development of standardized taxonomies, making nursing contributions more visible and measurable. Ultimately, this research will highlight the value of nursing care in NLC and S&T settings, providing an evidence base to drive policy changes that improve both health care outcomes and resource efficiency. Conclusions: This study lays the groundwork for health care policy reforms by advocating for the recognition, measurement, and funding of nursing contributions, ultimately enhancing patient outcomes and the sustainability of health systems.